Determination and correlation of solubility and thermodynamics of mixing of 4-aminobutyric acid in mono-solvents and binary solvent mixtures. (November 2016) - Zhao, Kaifei; Yang, Peng; Du, Shichao; Li, Kangli; Li, Xiaona; Li, Zhenfang; Liu, Yumin; Lin, Lanlan; Hou, Baohong; Gong, Junbo
Highlights: The solubility of 4-aminobutyric acid in mono-solvents and binary solvent mixtures were experimentally determined. The solubility data in five mono-solvents were correlated by three models. Four models were employed to correlate solubility data in methanol + water binary solvent mixtures. Solution mixing thermodynamics were calculated and the dissolution process were discussed. Abstract: A laser monitoring dynamic method was used to determine the solubility of 4-aminobutyric acid in five mono-solvents of methanol, formamide, 1, 2-propanediol, 1, 3-propanediol and water, and (methanol + water) binary solvent mixtures over the temperature ranging from 283.15 K to 323.15 K at atmospheric pressure. It turns out to be that in different mono-solvents, the solubility of 4-aminobutyric acid is temperature dependent and increases with the increasing temperature. While in (methanol + water) binary solvent mixtures, the solubility is positively correlated with temperature and negatively correlated with the mole fraction of methanol. The modified Apelblat equation, λh equation and NRTL_Binary model were employed to correlate the solubility data in five mono-solvents. While in (methanol + water) binary solvent mixtures, the NRTL_Ternary model, CNIBS/R-K model and Jouyban-Acree models were applied. It is found that the correlated results are in good agreement with the experimental results. Furthermore, with the activity coefficients considered, solution mixing thermodynamics were calculated and the dissolution process of 4-aminobutyric acid is also discussed.